Developing Critical Literacy Scoring Rubrics to Assess EFL Student's Critical Literacy Skills - Rizqiani, Diyah Ayu; Sailun, Betty; Herlina, Sari (Universitas Sarjanawiyata Tamansiswa, 2024)
Critical literacy skills are essential for EFL students to effectively engage with and analyze diverse texts in an increasingly globalized world, yet assessing these skills in non-native English speakers presents unique challenges. This study aimed to develop and validate comprehensive rubrics for assessing critical literacy skills in EFL contexts, addressing a significant gap in current assessment practices. This study employs 4D model (Thiagarajan et al. (1974) on instructional development. It consisted of four phases: Define Phase, Design Phase, Development Phase, and Dissemination Phase. The instrument of this study was a set of a critical literacy rubrics encompassing five dimensions: clarity of format, clarity of content, clarity of scoring, readability, and clarity of language. The research participants in the current study were 50 students of English Language Education Study Program, two Critical Reading lecturers, and two experts as the instrument validators. The rubrics demonstrated sensitivity to different proficiency levels and effectively captured the multifaceted nature of critical literacy in EFL contexts. This study contributes a validated, comprehensive tool for assessing EFL students' critical literacy skills, with significant implications for enhancing critical literacy instruction, curriculum development, and further research in EFL education, ultimately equipping students with the necessary skills to become critically engaged global citizens. Keywords: critical literacy, critical literacy skills, critical literacy rubric, EFL students.